ANALISIS PROSES BISNIS : STUDI KASUS BAGIAN CUSTOMER CARE PADA PT. TELKOM INDONESIA TBK – KANDATEL PONTIANAK - Windy Agasia; Susanti Margaretha Kuway (SISFOTENIKA, 2012)
Abstract: PT. Telkom Tbk – Kandatel Pontianak is one of biggest Government Owned Company (BUMN) which service is in telecomunication service for public in Indoeisa. Business process in Customer Care department is to know the quality of customer service, how much the dependence of Customer Care to the use of technology is, and what the respond of customers for the service given by Customer Care is. Research type used in this paper is descriptive methode according to facts taken from Customer Care department of PT. Telkom Tbk – Kandatel Pontianak. Data collecting methode used in this paper is primary data taken directly from respondent by using questioners and interviews. The methode used is business process analysis with data analysis strategy in form of business area analysis. The conclusion that can be taken from this research is that running business process for Customer Care department can be seen in the availability of interrelationship between business functions and business units. Each business functions have their own tasks and responsibilities. Every executive members in Customer Care department have their roles and relations with their business functions. Mapping of business functions vs organisational units matrix is used so that every activities in organisational functions become clear. Those activities are create, read, update and delete. Keywords : Business Function Decomposition, Matrix Analysis, Critical Success Factor, Business Process Analysis, Entity Relationship Diagram